ASTRONOMICAL ANGLE MEASUREMENT WITH THE USE OF NEWTONIAN TELESCOPE AND DSLR CAMERA (PANGEEA, 2025)
Our task is to measure angles for astronomical purposes using a Newtonian telescope and a DSLR camera. The paper includes overview of the construction and imaging of astronomical telescopes, instruments and DSLR cameras. The aim is to go beyond numerical estimations to the determination of real values by measurements. From these measurements various conclusions can be drawn: the variation in the apparent size of the Moon due to its motion in an elliptical orbit, which can be used to infer the eccentricity of the orbit, the ratio of the distance of the perigee and apogee from the focal point, and the determination of the celestial velocity of the Moon, compared with its calculated value.
Keywords: Astronomy; angle measurement; telescope; DSLR camera